Technology for sustainable development - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2012)
The technical and technological expansion of man in the natural environment constitutes an important component of the ecological debate. The debate shows the initial confrontation of the antagonized positions. The radical critics of technology rejected the then-contemporary technical and industrial system and supported “alternative technology”, whereas the radical promoters of this system represented a naive belief in the unlimited progress of science and technology. After some time this debate was enriched by a new idea: sustainable development. It proposes seeking new solutions to the technical and technological presence of man in the natural environment. These solutions are expressed by a proportionally balanced synthesis of both positions. The purpose should be to find a way that would be a compromise between the development of technology and the demands of nature.